Lithic resources as a proxy for the social use of territory among hunter-gatherers of Central Chile - Cornejo Bustamante, Luis Eduardo; Cornejos, Patricio Galarce; Villanueva, Miguel Saavedra; Riquelme, Lorena Sanhueza (Journal of Lithic Studies, 2020)
This paper presents the results of a study of the composition of lithic raw materials from the contexts of archaeological sites of hunter-gatherers of Central Chile (latitudes 33° to 34.5° S) between 5000 to 1000 years BP. This territory is characterized by a wide distribution of certain coarse and medium-grained lithic raw materials (andesite, basalt and granite), preferably used in low formatted tools, and the specific location of those of fine grain (obsidian and siliceous rocks), suitable for bifacial reduction, only in some localities. In this analysis, 22 sites have been included, each of which presents different proportions of these raw materials in their context, a set that, when analysed in terms of the diversity of each case, generated clear spatial groupings which were ratified by means of a principle component analysis. These groupings of sites are located in direct association with the lithic landscape of different localities within the region, although we propose that the simple cost-benefit explanation would not account for their formation. According to the authors, these groups would be marked by behaviours that can only result from social restrictions on access to certain sources of these raw materials, especially considering that the distances between their location and the position of the different sources in several cases is not too large to be considered a factor in itself. These restrictions could be interpreted as the existence of socially different groups within the study area, a question that is compared with ethnographic data currently available on the size of the territories of different groups of hunter-gatherers and their annual mobility ranges.